Nomophobia Among Adolescents: The Role of Hadith in Overcoming Nomophobia in Adolescents Through Character Education - Arif, Mohammad; Rahma, Vika Faiza (Pascasarjana Universitas KH. Abdul Chalim, 2024)
Nomophobia, or fear and anxiety about not having access to a cell phone, has become a common phenomenon among teenagers. Teenagers' dependence on technology, especially smartphones, has led to the emergence of nomophobia as a result of losing control of accurate information. The negative impacts of nomophobia include high stress, loss of focus, and anti-social tendencies. This research aims to examine the role of hadith in overcoming nomophobia in adolescents through character education. As a source of inspiration and guidance, Hadith can help teenagers develop better character and overcome homophobic tendencies. The method used in this research is a literature study, which collects data and reviews it from relevant reference sources, which are then connected to research to describe the problem formulation. The results of this research explain how a clearer picture of hadith can help teenagers overcome nomophobia and increase awareness of culture and social context.